Evaluation of capacity to deliver emergency obstetrics and newborn care updated midwifery and reproductive health training curricula in Kenya: Before and after study - Duncan N. Shikuku; Edna Tallam; Ibrahim Wako; Agnes Mualuko; Lucy Waweru; Lucy Nyaga; Issak Bashir; Charles Ameh (Elsevier, 2022)
Introduction: Provision of emergency obstetric and newborn care (EmONC) by skilled health personnel reduces maternal and newborn mortality. Pre-service diploma midwifery and clinical medicine (reproductive health) curricula in Kenya were reviewed and updated integrating the competency based EmONC curriculum. A two-part (virtual for theoretical component and face-to-face for the skills-based component) capacity building workshop for national midwifery/clinical medicine trainers of trainers to improve their capacity to implement the updated curricula and cascade it to colleagues nationwide was conducted. Purpose: This paper measured change in confidence of pre-service midwifery/clinical medicine educators to deliver the updated competency-based curricula in Kenya. Methods: A before-after study among 51 midwifery/clinical medicine educators from 35 training colleges who participated in upskilling workshops as trainers-of-trainers for the updated curricula between September-November 2020. Assessment included self-reported confidence using a 3-point Likert scale (not confident, somewhat confident or extremely confident) in facilitating online teaching (as COVID-19 pandemic containment measure), EmONC skills teaching/demonstration; scenario/simulation teaching, small group discussions, peer review and giving effective feedback. Analysis involved test of proportions with p-values < 0.05 statistically significant. Results: Educators' confidence significantly improved in facilitating virtual teaching (46% to 70%, p = 0.0082). On the competency-based training, the confidence among educators significantly increased in facilitating EmONC skills teaching/demonstration (44% to 96%), facilitating scenario/simulation teaching (46% to 92%), facilitating small group discussions (46% to 94%), giving effective feedback (46% to 92%), and peer review and feedback (47% to 77%), p < 0.05). Conclusion: The blended training improved the confidence of pre-service educators to deliver the updated midwifery/clinical medicine curricula.